Faktor-Faktor yang Berhubungan dengan Kejadian Post Anasthesia Shivering pada Pasien Pasca Spinal Anasthesia di RSUD Bangil - Sholehah, Ummatus; Ciptaningtyas, Maria Diah; Yuswanto, Tri Johan Agus Agus (FORIKES, 2023)
Spinal anesthesia is a type of anesthesia that is injected into the cerebrospinal fluid (CSF) when the patient is about to undergo surgery. Spinal anesthesia causes hypothermia which triggers shivering. Shivering is the body's attempt to increase heat production and increase body temperature. To determine the factors associated with the incidence of post-anesthesia shivering in post-spinal anesthesia patients. Correlation research with a cross sectional approach. The research sample is 73 respondents using accidental sampling data collection technique. This study used the Chi-Square test, point biserial and logistic regression test as statistical analysis tests. The results of the logistic regression test showed that the duration of surgery was the top factor in the modeling, then BMI and ambient temperature. Factors that were not included in the modeling were gender, age, ASA status, type of surgery, comorbidities, and preoperative body temperature. There is a relationship between body mass index, duration of surgery, ambient temperature and the incidence of post-anesthesia shivering and there is no relationship between gender, age, type of surgery, comorbidities, and preoperative body temperature with shivering. The duration of surgery is the factor that is most related to the incidence of post-anesthesia shivering in post-spinal anesthesia patientsKeywords: post-spinal anesthesia patients; shivering factors; post anaesthesia shivering ABSTRAK Spinal anasthesia adalah salah satu jenis anastesi yang disuntikkan ke cairan serebrospinal (csf) saat pasien akan menjalankan operasi. Anestesi spinal menyebabkan hipotermia yang memicu terjadinya shivering. Shivering adalah upaya tubuh untuk meningkatkan produksi panas dan meningkatkan suhu tubuh. Untuk mengetahui faktor yang berhubungan dengan kejadian post anasthesia shivering pada pasien pasca spinal anasthesia. Penelitian korelasi dengan pendekatan cross sectional. Sampel penelitian berjumlah 73 responden dengan teknik pengambilan data accidental sampling. Penelitian ini menggunakan uji Chi-Square, point biserial dan uji regresi logistik sebagai uji analisis statistik. Hasil uji regresi logistik didapatkan hasil lama pembedahan merupakan faktor yang paling atas masuk pemodelan kemudia IMT dan suhu lingkungan. Faktor yang tidak masuk pemodelan yaitu jenis kelamin, usia, status ASA, jenis pembedahan, komorbid, dan suhu tubuh preoperasi. Ada hubungan antara faktor indeks masa tubuh, lama pembedahan, suhu lingkungan dengan kejadian post anasthesia shivering serta tidak ada hubungan antara jenis kelamin, usia, jenis pembedahan, komorbid, dan suhu tubuh pre operasi dengan kejadian shivering. Lama pembedahn merupakan faktor yang paling berhubungan dengan kejadian post anasthesia shivering pada pasien pasca spinal anasthesiaKata kunci: pasien pasca spinal anasthesia; faktor-faktor shivering; post anasthesia shivering